A Theory Of Planned Behavior And Transformational Leadership: An Examination Of Corporate Philanthropy In Malaysia'S Smes - Sim, Gaik Lan (2014)
According to SME Annual Report 2012 - 2013, Malaysia Small Medium Enterprises (SMEs) will become the nation's future engine of growth. In addition, the government had launched SME Master plan 2012 - 2020 which define the policy direction for SMEs companies toward achieving Malaysia's goal of becoming high income nation by 2020. Despite the important role play by SMEs companies, little attention has been given to understand these groups of company engagement in corporate philanthropy. The involvement by SMEs companies in corporate giving is critical in order to ensure Malaysia become a caring nation by 2020. This study intends to examine the determinants of SMEs corporate philanthropy decision. Ajzen's theory of planned behavior (TPB) and Bass's transformational leadership theory which have been validated in many academic fields will provide the theoretical foundation for a further understanding of SMEs companies' philanthropic behaviors. Moral obligation and government incentives were also included to provide a more complete study. The study was carried out using 82 questionnaires answered by SMEs companies' top management.